APPLICATION OF ORGANIC FERTILIZER RICE WASHING AND WATER PRUNING OF TOMATO (Lycopersium esculentum Mill) FOR OPTIMUM GROWTH AND RESULTS - Hamidah Hamidah (Agrifarm : Jurnal Ilmu Pertanian, 2020)
ABSTRACT Organic farming continues to grow in line with the rapid market demand for organic fruit and vegetables. In our country, organic agriculture is experiencing rapid development due to the fact that agricultural products, especially fresh vegetables and fruit, are grown using organic farming systems. Organic agricultural products are starting to attract consumers, especially the upper middle class, who are willing to pay more for food products that are healthy, safe, and environmentally friendly. The purpose of this study was to determine the use of organic fertilizers for washing rice water and pruning water shoots on the growth and yield of tomato plants. The research was conducted in Gunung Kelua village, Samarinda, East Kalimantan for approximately 4 (four) months, from March to July 2020. This study used a randomized block design arranged 3x2 factorial with 3 replications. The first factor is liquid organic fertilizer which consists of 3 (three) levels, including: P0 Without Treatment, P1 (Liquid Organic Fertilizer 250 ml / l water), P2 (Liquid Organic Fertilizer 500 ml / l water). The second factor is pruning water shoots consisting of 2 (two), namely T0 without pruning water shoots on tomato plants, T1 by pruning water shoots on tomato plants. The results showed that the application of liquid organic fertilizer had no significant effect on plant height, but had a significant effect on the number of fruits and production.